Addressing Temporal Instability in Drum Learning through Deliberate Practice: An Educational Intervention Study - Piter Sembiring; Marsel Ridky Maulana (Pendidikan Seni Musik, Fakultas Pendidikan Seni dan Desain, Universitas Pendidikan Indonesia, 2026)
This study investigates the development of rhythmic control in drum learning through deliberate practice. The study addresses temporal instability, a common problem in early drum performance characterized by rushing, dragging, and inconsistent timing during repetitive execution. A qualitative educational intervention design was employed involving 15 students aged 9–12 years in a private drum learning setting. Data were collected through observations, performance recordings, and interviews across four instructional cycles. The findings indicate that rhythmic control develops through structured and error-focused practice rather than repetition alone. Tempo reduction, pattern segmentation, and immediate feedback enabled students to identify timing errors, improve temporal stability, and maintain synchronization with the metronome. Across the intervention, students demonstrated greater self-correction, improved timing awareness, and more consistent rhythmic performance. The findings suggest that rhythmic control involves not only tempo accuracy but also temporal self-regulation and integrated musical understanding. This study contributes to music education by proposing a developmental framework for rhythmic control in drum learning. The findings may serve as a pedagogical reference for drum educators in designing systematic instructional strategies to support rhythmic development and self-regulated learning